2016
DOI: 10.3389/fmicb.2016.01904
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Compounds-Macrolactin Alters the Soil Bacterial Community and Abundance of the Gene Encoding PKS

Abstract: Macrolactin produced by many soil microbes has been shown to be an efficient antibacterial agent against many bacterial pathogens. However, studies examining the effect of macrolactin on both the soil bacterial community and the intrinsic bacterial species that harbor genes responsible for the production of this antibiotic have not been conducted so far. In this study, a mixture of macrolactin was isolated from the liquid culture of Bacillus amyloliquefaciens NJN-6, and applied to the soil once a week for four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…Still, loss of diversity can be expected when exposing microbial communities to compounds with antibiotic properties, as several studies on the effects of commercial antibiotics on gut microbiota have demonstrated ( Dethlefsen and Relman, 2011 ; Zaura et al, 2015 ). In fact, when a soil community was exposed to weekly pulses of the natural antimicrobial macrolactins (∼2.5 μg/g soil) a 16% loss in alpha diversity (chao1) was observed over 4 weeks ( Yuan et al, 2016 ) – a considerably milder impact than the one herein reported over a shorter exposure period.…”
Section: Resultsmentioning
confidence: 53%
“…Still, loss of diversity can be expected when exposing microbial communities to compounds with antibiotic properties, as several studies on the effects of commercial antibiotics on gut microbiota have demonstrated ( Dethlefsen and Relman, 2011 ; Zaura et al, 2015 ). In fact, when a soil community was exposed to weekly pulses of the natural antimicrobial macrolactins (∼2.5 μg/g soil) a 16% loss in alpha diversity (chao1) was observed over 4 weeks ( Yuan et al, 2016 ) – a considerably milder impact than the one herein reported over a shorter exposure period.…”
Section: Resultsmentioning
confidence: 53%
“…All qPCR amplifications were performed on the Applied Biosystem 7,500 Real‐Time PCR System (ABI) using SYBR Premix Ex Taq (TliRnaseH Plus) (TaKaRa Biotechnology Co., Ltd). Protocols for qPCR were performed as previously described using the primers 347F: 5′‐GGAGGCAGCAGTRRGGAAT‐3′ and Bact531R: 5′‐CTNYGTMTTACCGCGGCTGC‐3′ (Yuan et al, 2016). Quantitative PCR was performed for the three technical replicates for every sample, and amplification specificity was verified by melt‐curve analysis and agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…The mode of action of macrolactin-A is probably due to phosphatase inhibitory action. Potent in vitro inhibitory action against Herpes simplex virus and HIV has been explored [ 43 ].…”
Section: Introductionmentioning
confidence: 99%